Comfortable housing model in new housing PPRT for Orang Asli - Ahmad, Mohd. Hamdan; Kandar, Mohd. Zin (Faculty of Built Enviroment, 2007)
This research investigates the proposed comfortable housing model as thermal comfort strategy in orang asli house in Malaysia. The Government has implemented specific development programmes for the indigenous community or the orang asli, which included economic and social programmes to improve their standard of living. One such special programme is called the Hard-Core Poor Development Programme (PPRT).The new PPRT house initiated by the government is not only small but has heat-trapping zinc roofs and concrete walls. This house indicated uncomfortable condition compare to the existing orang asli house. Unfortunately, the architectural design solutions do not permit good passive cooling for thermal comfort. This can be illustrated by the high indoor temperature experienced during the day time. In this research, Proposed Comfortable PPRT House Model has been suggested by adopting traditional orang asli house element and lifestyle as much as possible as alternative techniques for achieving passive cooling. The thermal comfort study in this research involved the use of computer simulation using Integrated Environment Solution (IES) technique. The specific software called Apache is used. Validation of IES Apache is done by comparing the computer simulation result with the field measurement result on existing house model. The result of the Proposed Comfortable PPRT House Model showed that the house model increased thermal comfort performance by reducing air temperature (until 2Â°C) and PMV index (until 1). The other important factor is that it can continuously maintain the comfortable condition in mid day regardless of the available outside climate condition. This effect is significant toward improving the thermal comfort performance of PPRT house designed for orang asli through passive cooling, thus provide comfortable healthy and low energy house.